HUBUNGAN KEPATUHAN DIET TERHADAP KADAR GULA DARAH PUASA PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS SUKARASA KOTA BANDUNG - Siti Najwa Nurhaliza; Nitta Isdiany; Yohannes Willihelm Saleky; Agustina Indri Hapsari; Putu Bunga Fitridewi (Jurusan Gizi Poltekkes Kemenkes Bandung, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that requires appropriate dietary management to maintain stable blood glucose levels. This study aimed to determine the relationship between patients' knowledge, dietary compliance, and fasting blood glucose levels among individuals with type 2 diabetes mellitus at Sukarasa Primary Health Center, Bandung, Indonesia. A cross-sectional study was conducted involving 30 respondents selected using simple random sampling. Data were collected using a knowledge questionnaire, a dietary compliance questionnaire, the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and fasting blood glucose measurements. Data were analyzed using the Chi-square test. The results showed that the majority of respondents (56.7%) had uncontrolled fasting blood glucose levels. Most respondents demonstrated good knowledge of diabetes mellitus (60.0%) and compliance with the recommended dietary regimen (56.7%). Statistical analysis revealed a significant association between knowledge and dietary adherence (p < 0.05), as well as between dietary adherence and fasting blood glucose levels (p < 0.05). However, no significant association was found between knowledge and fasting blood glucose levels (p > 0.05). In conclusion, better knowledge was associated with higher dietary adherence, although it was not directly associated with fasting blood glucose levels. Continuous nutrition education is recommended to improve dietary adherence as part of the management of type 2 diabetes mellitus.